Intrinsically Disordered Proteins Link Alternative Splicing and Post-translational Modifications to Complex Cell Signaling and Regulation. Issue 16 (3rd August 2018) - Zhou, Jianhong; Zhao, Suwen; Dunker, A. Keith
Abstract: Intrinsically disordered proteins and regions (IDPs and IDRs) lack well-defined tertiary structures, yet carry out various important cellular functions, especially those associated with cell signaling and regulation. In eukaryotes, IDPs and IDRs contain the preferred loci for both alternative splicing (AS) and many post-translational modifications (PTMs). Furthermore, AS and/or PTMs at these loci generally alter the signaling outcomes associated with these IDPs or IDRs, where the functional cooperation of these three features is named the IDP–AS–PTM toolkit. However, the prevalence of such functional modulations remains unknown. Also, the signal-altering mechanisms by which AS, and PTMs modulate function and the extent to which AS and PTMs collaborate in their signaling modulations have not been well defined for particular protein examples. Here we focus on three important signaling and regulatory IDR-containing protein families in humans, namely, G protein-coupled receptors (GPCRs), which are transmembrane proteins; the nuclear factors of activated T cells (NFATs), which are transcription factors; and the Src family kinases (SFKs), which are signaling enzymes. The goals here are to determine how AS and PTMs individually alter the outcomes of the signaling carried out by the various IDRs and to determine whether AS and PTMs work together to bring about differential cellular responses. We also present data indicating that a wide range of other signaling IDPs or IDRs undergo both AS- and PTM-based modifications, suggesting that they, too, likely take advantage of signal outcome modulations that result from collaboration between these two events. Hence, we propose that the widespread cooperation of IDPs, AS and/or PTMs provides an IDP–AS–PTM toolkit and substantially contributes to the vast complexity of eukaryotic cell signaling systems. Graphical abstract: Unlabelled Image Highlights: We propose that IDPs work in concert with AS and PTMs to provide an IDP–AS–PTM toolkit for complex context-dependent cell signaling and regulation. Three intensely studied, highly divergent signaling protein families, namely, G protein-coupled receptors (GPCRs), nuclear factor of activated T-cell (NFAT) transcription factors and Src family kinases (SFKs), all use this toolkit to increase context-dependent signaling complexity. PubMed text mining shows the widespread occurrence of IDPs, AS and PTMs in a large number of proteins including those involved in developmental signaling pathways, which indicates a common maybe even universal use of the IDP–AS–PTM toolkit in eukaryotic multicellular signaling systems.